Reaching and Grasping Training Improves Functional Recovery After Chronic Cervical Spinal Cord Injury - Gallegos, Chrystine; Carey, Matthew; Zheng, Yiyan; He, Xiuquan; Cao, Qi Lin (Frontiers in Cellular Neuroscience, 2020)
Previous studies suggest locomotion training could be an effective non-invasive therapy after spinal cord injury (SCI) using primarily acute thoracic injuries. However, the majority of SCI patients have chronic cervical injuries. Regaining hand function could significantly increase their quality of life. In this study, we used a clinically relevant chronic cervical contusion to study the therapeutic efficacy of rehabilitation in forelimb functional recovery. Nude rats received a moderate C5 unilateral contusive injury and were then divided into two groups with or without Modified Montoya Staircase (MMS) rehabilitation. For the rehabilitation group, rats were trained five days a week starting at 8 weeks post-injury (PI) for 6 weeks. All rats were assessed for skilled forelimb functions with MMS test weekly and for untrained gross forelimb locomotion with grooming and horizontal ladder tests bi-weekly. Our results showed that MMS rehabilitation significantly increased the number of pellets taken at 13 and 14 weeks PI and the accuracy rates at 12 to 14 weeks PI. However, there were no significant differences in the grooming scores or the percentage of horizontal ladder mis-steps at any time points. Histological analyses revealed that MMS rehabilitation significantly increased the number of serotonergic fibers and the amount of presynaptic terminals around motor neurons in the cervical ventral horns caudal to the injury and reduced GFAP-immunoreactive astrogliosis in spinal cords caudal to the lesion. This study shows that MMS rehabilitation can modify the injury environment, promote axonal sprouting and synaptic plasticity, and importantly, improve reaching and grasping functions in the forelimb, supporting the therapeutic potential of task-specific rehabilitation for functional recovery after chronic SCI.